New Readings of Anselm of Canterbury's Intellectual Methods
1 online resource.
Keywords: These essays present new readings of Anselm’s speculative and spiritual writings on topics including his relationship to Augustine, proofs for God’s existence, faith and reason, human freedom and the problem of evil, his spiritual meditations and prayers, as well as Anselm’s reception by 19th and 20th century thinkers, modernism, and feminism. These philosophical, theological and literary analyses bring fresh perspectives on Anselm both in his historical context and in dialogue with contemporary questions. Contributors are: Tomas Ekenberg, Riccardo Fredriga, Emery de Gaál, Kyle Philip Hubbard, Maggie Ann Labinski, Roberto Limonta, Ian Logan, Gavin Ortlund, M.B. Pranger, Gregory B. Sadler, Kevin Staley, Karen Sullivan, Eileen C. Sweeney, Michael Vendsel, Luca Vettorello, James Wetzel, and Kevin White.